Effects of Prior Phonotactic Knowledge on Infant Word Segmentation: The Case of Nonadjacent Dependencies - Gonzalez-Gomez, Nayeli; Nazzi, Thierry (Journal of speech, language, and hearing research, 2013)
Purpose: In this study, the authors explored whether French-learning infants use nonadjacent phonotactic regularities in their native language, which they learn between the ages of 7 and 10 months, to segment words from fluent speech. Method: Two groups of 20 French-learning infants were tested using the head-turn preference procedure at 10 and 13 months of age. In Experiment 1, infants were familiarized with 2 passages: 1 containing a target word with a frequent nonadjacent phonotactic structure and the other containing a target word with an infrequent nonadjacent phonotactic structure in French. During the test phase, infants were presented with 4 word lists: 2 containing the target words presented during familiarization and 2 other control words with the same phonotactic structure. In Experiment 2, the authors retested infants' ability to segment words with the infrequent phonotactic structure. Results: Ten- and 13-month-olds were able to segment words with the frequent phonotactic structure, but it is only by 13 months, and only under the circumstances of Experiment 2, that infants could segment words with the infrequent phonotactic structure. Conclusion: These results provide new evidence showing that infant word segmentation is influenced by prior nonadjacent phonotactic knowledge. (Contains 2 figures, 1 table, and 2 footnotes.)